Transgene insertion affects transcription and epigenetic modification of flanking host sequence in transgenic pigs - Kong, Q. R.; Wu, M. L.; Zhang, L.; Wang, F.; Yin, Z.; Mu, Y. S.; Liu, Z. H. (Cellular and Molecular Biology, 2011)
Transgenic technology has been used for years to study gene function, produce important proteins, and generate models for the study of human diseases. However, the efficiency of producing transgenic animal lines that retain normal function is extremely low. The low efficiency can be mainly attributed to the integrated transgene. A further understanding of the effects of transgene integration on transcription and epigenetic modification of the host genome would improve the transgenic efficiency. Therefore, we utilized three transgenic pigs produced by SCNT expressing GFP, to identify alterations of transcription, DNA methylation and histone acetylation resulting from integration of the GFP gene. Multiple copies of the transgene integrated into a single site of the three transgenic pigs were verified by TAIL-PCR and the integration sites were different in each pig. We observed that the integrated transgene frequently resulted in significantly low transcription of flanking sequences in various tissues of transgenic pigs in comparison with wild-type pigs. Corresponding with the low transcription, DNA hypermethylation and loss of acetylation of histone H3 and H4 were detected. Our results demonstrate that the abnormal transcription and epigenetic modification of sequences flanking the transgene were not correlated with the expression of the transgene. However, the disturbance caused by the insertion of the transgene, was dependent upon the integration site. This suggests that some sequences in the host genome could permit integration and expression of transgene without causing defects in the host.